Interrogating the domestic approach of Nigeria’s counterterrorism strategy under president Goodluck Jonathan’s Administration, 2009- 2015 - Ogundeji, Olusegun Emmanuel; Popoola, Abayomi; Fyanka, Bernard B. (Corpus Intellectual, 2025)
Terrorism in northern Nigeria has remained persistent despite government’s counterterrorism efforts. Hundreds of souls have been killed, settlements have been deserted, and lots of families have been internally displaced. While the havoc of terrorism is well known, the dynamics of the socio-religious factors that initiated them have not been well studied. It is against this backdrop that the study seeks to investigate the domestic approach of Nigeria’s counterterrorism strategy under President Goodluck Jonathan’s administration. It will also discuss the origin and causes of terrorism in Nigeria. To achieve its aim, the paper explores the terrorism prevention theory to conceptualize and explain its findings. Furthermore, it defines some terms and also explains the types of terrorism for better comprehension of the discourse. The paper employs both primary and secondary source materials.